Morphological description and nutritional of fruits of rambutan (Nephelium lappaceum). - Vargas-Calvo, Alfonso (Agronomía Mesoamericana, 2003)
The study was conducted with the rambutan (Nephelium lappaceum) cultivars R-134, R-162, R-167, Jitlee and Rongrien. All cultivars showed red oval fruits with spines, which turned red later than the rind did. The fruit weigth (32.7 to 37.3 g), flesh per fruit (40.8 to 51.9%), Brix (18.3 to 18.6) and the easily flesh removal from the seed, agreed with the quality standards for fresh fruit export or canning. The N was the most abundant nutrient in the fruit (77 to 87 mg), followed in decreasing order by K (63 to 81 mg), Ca (22 to 31 mg), P (11 to 13 mg), Mg (9 to 13 mg) and S (4 to 6). The contents of Fe, Cu, Zn, Mn and B were small (lower than 0,38 mg).